A study of multi-frequency electromagnetic responses on steel grain boundaries using 3D micro and macro FE models - Jianing Zhao; Jialong Shen; Xi Liu; Yufeng Chen; Chen Zhang; Zhengbing Meng; Lei Zhou (Materials & Design)
Microstructures of steels has a decisive influence on its mechanical properties, among which the microscopic component of grain boundary is particularly important. In this study, based on multi-frequency electromagnetic detection technology, the 3D micro-model including grain boundary components are constructed. Effects of different phases, grain sizes and grain boundaries on the electromagnetic response are discussed by combining with the macro-sensor model. The results show that the low-frequency inductance increases with the increase of ferrite grain boundaries thickness and grain sizes., Grain boundaries with different orientations show different electromagnetic responses. The low-frequency inductance values of the model with grain boundaries are closer to the experimental values under different ferrite fractions.